An exploratory study on differences in maternal care between two ecotypes of Nigerian indigenous chicken hens - Oyeniran, Victor J.; Iyasere, Oluwaseun S.; Durosaro, Samuel O.; Fasasi, Fasasi B.; Odetayo, Peace O.; Ogunfuyi, Sulaiman A.; Odetunde, Paul O.; Akintayo, Taiwo C.; Daramola, James O. (Frontiers in Veterinary Science, 2022)
The Yoruba (YR) and Fulani (FL) are the two notable indigenous chicken ecotypes in Nigeria. They exhibit broodiness and post-hatch care of their chicks. Maternal behaviors of these two ecotypes are scarce, hence the need for this study. Separate flocks of these ecotypes were kept at the same research station. Hens that became broody (ten YR and five FL) were separated and monitored until 3rd-week post-hatch. Behaviors such as sitting on eggs, eyes opening or closing while sitting on the egg, feeding, drinking, and egg turning were monitored for 3 days in the 1st and 2nd weeks of brooding and daily in the 3rd week of brooding. Behaviors were monitored for 6 h/day (07:00-09:00h, 11:00-13:00h and 15:00-17:00h). Chicks hatched by these hens were subjected to tonic immobility (TI) tests on the 7th, 14th, and 21st days post-hatch to determine their level of fear. Data collected were analyzed for each week using Mann-Whitney U-test. The YR hens sat for a longer time on the eggs at the 1st (U = 125.500, z = -2.281, P = 0.013), 2nd (U = 112.500, z = -2.858, P = 0.004) and 3rd (U = 87.500, z = -3.320, P = 0.001) weeks. While sitting on their eggs, the YR hens opened their eyes for a longer period at the 1st (U = 142.500, z = -2.138, P = 0.033) and 3rd (U = 120.000, z = -2.542, P = 0.011) weeks of brooding. Feeding, drinking and egg turning frequencies were similar (P > 0.05) in the two ecotypes. At the 7th day post-hatch, the duration of TI was shorter (U = 323.500, z = -2.829, P = 0.005) in the FL than YR chicks. On the 14th day post-hatch, the number of attempts to induce TI was lesser in the YR than in FL chicks (U=376.000, Z= -2.267, P=0.023). On the 21st day post-hatch, YR and FL had a similar (P>0.05) fear level. In conclusion, YR hens sat longer with eyes opened during brooding. Chicks of both ecotypes showed different levels of fear in the first two weeks of life.